Mechanochemical synthesised solid electrolyte based on Li2O: electrical and structural properties / Ahmad Fuzairi Ahmad Faizal - Ahmad Faizal, Ahmad Fuzairi (2014)
This study involved the fabrication of lithium ion solid electrolyte in the Li2O-TiO2-P2O5 (LTP) system. All samples were prepared using mechanical milling (MM)method. The precursor TiO2-P2O5 (TP) system were first fabricated and characterized by Electrochemical Impedance Spectroscopy (EIS), X-Ray Diffractometer (XRD), Field Emission Scanning Electrone Microscope (FESEM) and laser particle sizer. The highest room temperature conductivity was obtained for 60 wt.% of TiO2-40 wt.% of P2O5 (TP 40) and TP 40 sintered at 900 °C (TP 900) with values of 3.18 x 10-7 Scm-1 and 8.13 X 10-7 Scm-1 respectively. XRD studies showed presence of TiP2O7 peaks in the diffraction pattern of TP 40 as well as TP 900. FESEM micrographs showed agglomeration of the samples as the sintering temperature changed indicating availability of big and small grains. Small grains increased as sintering temperature increased. The size of the particle of the TP samples were estimated to range from 0.70 µm to 3.01 µm for sintered and unsintered samples. In the LTP system, the highest conductivity obtained for the unsintered sample, LTP 15 and sintered LTP 15 (LTP 900) is 6.89 x 10-6 Scm-1 and 3.03 x 10-5 Scm-1 respectively. The diffraction pattern indicate the presence of LiTi2(P04)3 peaks which is the conducting phase.Small grains were observed in all sintered samples with increase in as sintering temperature increases. The sizes of particle of LTP samples were decreased to as low as 200 nm. Temperature dependance studied showed that the conductivity obeys Arrhenius rule indicating that the conductivity is thermally activated.